PAR-1 Antagonism to Promote Gut Mucosa Healing in Crohn's Disease Patients: A New Avenue for CVT120165. (15th November 2021) - Motta, Jean-Paul; Deraison, Celine; Le Grand, Sylvie; Le Grand, Bruno; Vergnolle, Nathalie
Abstract: A new paradigm has been added for the treatment of inflammatory bowel diseases such as Crohn's disease and ulcerative colitis. In addition to resolving symptoms and inflammatory cell activation, the objective of tissue repair and mucosal healing is also now considered a primary goal. In the search of mediators that would be responsible for delayed mucosal healing, protease-activated receptor-1 (PAR-1) has emerged as a most interesting target. Indeed, in Crohn's disease, the endogenous PAR-1 agonist thrombin is drastically activated. Activation of PAR-1 is known to be associated with epithelial dysfunctions that hamper mucosal homeostasis. This review gathers the scientific evidences of a potential role for PAR-1 in mucosal damage and mucosal dysfunctions associated with chronic intestinal inflammation. The potential clinical benefits of PAR-1 antagonism to promote mucosal repair in CD patients are discussed. Targeted local delivery of a PAR-1 antagonist molecule such as CVT120165, a formulated version of the FDA-approved PAR-1 antagonist vorapaxar, at the mucosa of Crohn's disease patients could be proposed as a new indication for IBD that could be rapidly tested in clinical trials. Lay Summary: The potential clinical benefits and indications of PAR-1 antagonism to treat inflammatory bowel diseases are discussed.